Characterization of ZnO-degraded varistors used in high-tension devices - Ramirez, M. A.; Simoes, A. Z.; Marquez, M. A.; Maniette, Y.; Cavalheiro, A. A.; Varela, José Arana [UNESP] (Elsevier B.V., 2007)
The effects of the degradation process on the structural, microstructural and electrical properties of ZnO-based varistors were analyzed. Rietveld refinement showed that the BiO2-x phase is affected by the degradation process. Besides the changes in the spinel phase, the degradation process also affects the lattice microstrain in the ZnO phase. Scanning electron microscopy analysis showed electrode-melting failure, while wavelength dispersive X-ray spectroscopy qualitative analysis showed deficiency of oxygen species at the grain boundaries in the degraded samples. Atomic force microscopy using electrostatic mode force illustrated a decrease in the charge density at the grain boundaries of the degraded sample. Transmission electron microscopy showed submicrometric spinel grains embedded in a ZnO matrix, but their average grain size is smaller in the degraded sample than in the standard one. Long pulses appeared to be more harmful for the varistors' properties than short ones, causing higher leakage current values. The electrical characteristics of the degraded sample are partially restored after heat treatment in an oxygen-rich atmosphere. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: ceramics; electron microscopy; electrical properties